NURSE COMPLIANCE IN IMPLEMENTING INTERVENTION PROCEDURES FOR HIGHRISK PATIENTS OF FALL IN INSTALATION AT CIMACAN HOSPITAL, CIANJUR REGENCY - Ricko Dwi Haryanto; Mokhamad Sandi Haryanto (Universitas Respati Yogyakarta, 2022)
The indicator of patient safety in hospitals is the reduction of the patient's risk of falling. The number of patients falling in Cimacan Hospital, Cianjur Regency, in 2015 was 7 patients and increased to 9 patients in 2016, nurses' compliance in implementing high-risk patient standards for falls is very important for patient safety. The purpose is to know the level of nurse compliance in the implementation of interventions for patients with a high risk of falling in Cimacan Hospital, Cianjur Regency. This study uses quantitative methods with an analytical descriptive design. Sampling with probability sampling using proportional stratified random sampling. The number of research samples is as many as 57 nurses. Results: most of the nurses (68.4%) were in the category of being obedient to the implementation of the intervention for patients with a high risk of falling. Based on each stage of the intervention procedure for high-risk patients, nurses were obedient in the pre-interaction stage (100%), orientation stage (89.5%), and documentation stage (100%) but at the implementation stage (63.2%) nurses did not comply. Suggestions to improve the standard implementation of high fall-risk patients so that the incidence of falls can be prevented or reduced.